Conformational changes in p53 analysed using new antibodies to the core DNA binding domain of the protein - Vojtesek, B; Dolezalova, H; Lauerova, L; Svitakova, M; Havlis, P; Kovarik, J; Midgley, C A; Lane, D P (Oncogene, 1995)
The p53 protein contains a protease resistant core section that binds to DNA in a sequence specific manner and whose crystal structure has been determined. This core is flanked at the N-terminus by the transcriptional transactivation domain and at the C-terminus by sequences involved in the oligomerisation of the protein. Extensive immunochemical analysis of p53 has shown that dominant antigenic sites lie within these N- and C-terminal domains while few antibodies to the central core have been identified. One of these, PAb240, has been extensively characterised as its epitope is cryptic in the native DNA binding core structure but is exposed by denaturation. This epitope is also exposed on many p53 proteins that contain point mutations in the core domain suggesting that these mutations may have a common affect on the structure of the core. To investigate this further we have generated several new antibodies to novel sites on p53 and mapped their epitopes using synthetic peptides. We find that antibodies to two other discrete sites in the core can also, like PAb240, recognize cryptic epitopes and distinguish mutant from wild-type conformations implying that the point mutations found in p53 in human tumours have widespread effects on the folding pattern of the DNA binding domain.
Keywords: Epitopes; Tumor Suppressor Protein p53; vazebná místa; sekvence aminokyselin; Antibodies, Monoclonal; lidé; Molecular Sequence Data; nádorové buňky kultivované; Amino Acid Sequence; molekulární sekvence - údaje; Protein Conformation; Tumor Cells, Cultured; Point Mutation; nádorový supresorový protein p53; bodová mutace; konformace proteinů; monoklonální protilátky; epitopy; Binding Sites; Humans